Compensation for land and building compulsorily acquired in Nigeria: A critique of the valuation technique. Issue 4 (27th July 2018) - Egbenta, Idu Robert; Udoudoh, Francis P.
Abstract : Purpose: Valuation for compensation on land and buildings compulsorily acquired for public purposes is statutory. The Land Use Act (LUA) of 1978 now cited as Laws of the Federation of Nigeria, CAP l5 LFN 2007, stipulates the use of Depreciated Replacement Cost (DRC) Method in the valuation for compensation purposes for building and installation. The purpose of this paper is to criticize the application of the DRC technique in the valuation by acquiring authority as it does not arrive at fair market value and adequate compensation in Nigeria. Design/methodology/approach: The method adopted for the study was a case study of real world valuation for compensation. Data used in the study were gathered mainly from government ministries and agencies responsible for land acquisition and compensation purposes. They included the Ministry of Lands and Housing, Land Use and Allocation Committee, and Ministry of Works and Transport. Market data on rental value, sales prices and other relevant data were collected from firms of professional that deal in real property. Findings: The result of the study reveals that valuation by acquiring authority using DRC methods as prescribed by the LUA does not reflect market value and it is inadequate to put the claimants in the position they were before the acquisition. As such, most victims expressed dissatisfaction with the amount paid to them, which sometimes result to crisis, conflict and prolonged litigation, resulting in delay in executing or abandonment of the intended project. Research limitations/implications: The study is limited to only one case study on acquisition and compensation for land and buildings with particular reference to Akwa Ibom State. This limitation does not invalidate the result as the law is applicable to the whole country. Practical implications: The implication is that the LUA needs to be review to fair market value as basis of valuation and payment for site value as well as the constitution to add "adequate" to Section 44 (1a). This will reduce the incidence of many communities and land owners protest against the decision of government or its agents to acquire their land for public purposes. Originality/value: The methodology meets the requirement of the law regarding compulsory land acquisition and compensation in Nigeria: The LUA of 1978. Using three scenarios: the valuation by acquiring authority, claimant's valuers and independent valuers to illustrate the critique of the methodology, the result shows the inadequacy of compensation.